Design, fabrication and characterization of tailored poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyexanoate] scaffolds by computer-aided wet-spinning. Issue 1 (2nd January 2018) - Puppi, Dario; Pirosa, Alessandro; Morelli, Andrea; Chiellini, Federica
Abstract : Purpose: The purpose of this paper is to describe the fabrication and characterization of poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyexanoate] (PHBHHx) tissue engineering scaffolds with anatomical shape and customized porous structure. Design/methodology/approach: Scaffolds with external shape and size modeled on a critical size segment of a rabbit's radius model and an internal macrochanneled porous structure were designed and fabricated by means of a computer-aided wet-spinning (CAWS) technique. Morphological, thermal and mechanical characterization were carried out to assess the effect of the fabrication process on material properties and the potential of the PHBHHx scaffolds in comparison with anatomical star poly(e-caprolactone) (*PCL) scaffolds previously validated in vivo . Findings: The CAWS technique is well suited for the layered manufacturing of anatomical PHBHHx scaffolds with a tailored porous architecture characterized by a longitudinal macrochannel. Morphological analysis showed that the scaffolds were composed by overlapping layers of microfibers with a spongy morphology, forming a 3D interconnected network of pores. Physical-chemical characterization indicated that the used technique did not affect the molecular structure of the processed polymer. Analysis of the compressive and tensile mechanical properties of the scaffolds highlighted the anisotropic behavior of the porous structure and the effect of the macrochannel in enhancing scaffold compressive stiffness. In comparison to the *PCL scaffolds, PHBHHx scaffolds showed higher compressive stiffness and tensile deformability. Originality/value: This study shows the possibility of using renewable microbial polyester for the fabrication of scaffolds with anatomical shape and internal architecture tailored for in vivo bone regeneration studies.